Analysis of the use of genomic DNA as a universal reference in two channel DNA microarrays - Gadgil, Mugdha; Lian, W.; Gadgil, Chetan J.; Kapur, V.; Wu, WS (BMC Genomics, 2005)
Background: DNA microarray is an invaluable tool for gene expression explorations. In the two-dye microarray, fluorescence intensities of two samples, each labeled with a different dye, are compared after hybridization. To compare a large number of samples, the 'reference design' is widely used, in which all RNA samples are hybridized to a common reference. Genomic DNA is an attractive candidate for use as a universal reference, especially for bacterial systems with a low percentage of non-coding sequences. However, genomic DNA, comprising of both the sense and anti-sense strands, is unlike the single stranded cDNA usually used in microarray hybridizations. The presence of the antisense strand in the 'reference' leads to reactions between complementary labeled strands in solution and may cause the assay result to deviate from true values. Results: We have developed a mathematical model to predict the validity of using genomic DNA as a reference in the microarray assay. The model predicts that the assay can accurately estimate relative concentrations for a wide range of initial cDNA concentrations. Experimental results of DNA microarray assay using genomic DNA as a reference correlated well to those obtained by a direct hybridization between two cDNA samples. The model predicts that the initial concentrations of labeled genomic DNA strands and immobilized strands, and the hybridization time do not significantly affect the assay performance. At low values of the rate constant for hybridization between immobilized and mobile strands, the assay performance varies with the hybridization time and initial cDNA concentrations. For the case where a microarray with immobilized single strands is used, results from hybridizations using genomic DNA as a reference will correspond to true ratios under all conditions. Conclusion: Simulation using the mathematical model, and the experimental study presented here show the potential utility of microarray assays using genomic DNA as a reference. We conclude that the use of genomic DNA as reference DNA should greatly facilitate comparative transcriptome analysis.

Amino acid abundance and composition in cell culture medium affects trace metal tolerance and cholesterol synthesis - Rawat, Jyoti; Bhambri, Aksheev; Pandey, Ujjiti; Banerjee, Sanchita; Pillai, Beena; Gadgil, Mugdha (Biotechnology Progress, 2023)
Amino acid compositions of cell culture media are empirically designed to enhance cell growth and productivity and vary both across media formulations and over the course of culture due to imbalance in supply and consumption. The interconnected nature of the amino acid transporters and metabolism suggests that changes in amino acid composition can affect cell physiology. In this study, we explore the effect of a step change in amino acid composition from a DMEM: F12-based medium to a formulation varying in relative abundances of all amino acids, evaluated at two amino acid concentrations (lean LAA vs. rich HAA). Cell growth was inhibited in LAA but not HAA. In addition to the expected effects on expression of the cell cycle, amino acid response and mTOR pathway genes in LAA, we observed an unanticipated effect on zinc uptake and efflux genes. This was accompanied by a lower tolerance to zinc supplementation in LAA but not in the other formulations. Histidine was sufficient but not necessary to prevent such zinc toxicity. Additionally, an unanticipated downregulation of genes in the cholesterol synthesis pathway was observed in HAA, accompanied by an increase in cellular cholesterol content, which may depend on the relative abundances of glutamine and other amino acids. This study shows that changes in the amino acid composition without any evident effect on growth may have profound effects on metabolism. Such analyses can help rationalize the designing of medium and feed formulations for bioprocess applications beyond replenishment of consumed components.
Keywords: Amino acids; cell culture medium; CHO cells; Cholesterol; zinc